Retrieving history: memory and identity formation in the early church - Laing, Stefana Dan (Evangelical ressourcement: ancient sources for the church's future, 2017)
Map -- Time line -- Invitation to the past -- Ancient historical writing and the rise of historical literary forms -- History as apologetic: harnessing a usable past -- Martyrology: remembering the martyrs' noble example -- Hagiography: martyrdom as discipleship in early Christian biographies -- Ecclesiastical history: the story of the church -- Conclusions and trajectories